2013
DOI: 10.5812/hepatmon.12787
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Octreotide on Urine Output During Orthotopic Liver Transplantation and Early Postoperative Renal Function; A Randomized, Double-Blind, Placebo-Controlled Trial

Abstract: BackgroundMaintenance of the adequate intraoperative renal perfusion is very important during Orthotopic Liver Transplantation (OLT) to prevent acute renal failure.ObjectivesFor the first time, this study was designed to survey the effects of octreotide on urine output during anesthesia for OLT and early postoperative renal function.Patients and MethodsIn this randomized double-blind placebo controlled clinical trial, 79 of 89 patients who underwent OLT and fulfilled the study requirement were randomly allocat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 21 publications
(25 reference statements)
0
20
0
2
Order By: Relevance
“…Twenty studies reporting on anesthetic strategies aiming at reducing postoperative morbidity and mortality were eventually included (Table 1) [22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41]. We retrieved 14 studies reporting on postoperative complications in patients undergoing liver transplantation [22][23][24]28,29,[31][32][33][35][36][37][39][40][41], five studies conducted in kidney recipients [26,27,30,34,38] and one reporting on lung recipients [25].…”
Section: Synthesis Of Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Twenty studies reporting on anesthetic strategies aiming at reducing postoperative morbidity and mortality were eventually included (Table 1) [22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41]. We retrieved 14 studies reporting on postoperative complications in patients undergoing liver transplantation [22][23][24]28,29,[31][32][33][35][36][37][39][40][41], five studies conducted in kidney recipients [26,27,30,34,38] and one reporting on lung recipients [25].…”
Section: Synthesis Of Resultsmentioning
confidence: 99%
“…Vasoactive drugs have been suggested to increase the splanchnic vascular tone, restore an adequate renal perfusion and be effective in 40-50% of patients with hepatorenal syndrome [60]. [37] investigated the protective effect of octreotide on renal function in 89 patients: the octreotide group had a significantly higher urine output, but there was no difference in the postoperative serum creatinine levels or need for RRT. Sahmeddini and coll.…”
Section: Acute Renal Failure After Liver Transplantationmentioning
confidence: 99%
“…Развитие асцита вследствие прогрессирования портальной гипертензии на ранней стадии заболевания или при первичном эпизоде декомпенсации ЦП имеет место в 20-75% случаев. Ультразвуковое исследование (УЗИ) является первым методом в диагностике ЦП и определении признаков развивающейся портальной гипертензии [5,6].…”
Section: Introductionunclassified
“…Most LT anesthesiologists have tended to use norepinephrine (NE), which is one of the powerful vasoconstrictors released by sympathetic nerve endings and one of the most widely used cardiovascular active drugs in clinical anesthesia, to maintain hemodynamic stability during LT anesthesia. Previous studies have shown that intraoperative application of vasoconstrictors could reduce the occurrence of postreperfusion syndrome (Ryu et al, 2012), improve renal perfusion (Fayed et al, 2013;Sahmeddini et al, 2013) and reduce the frequency of percutaneous interventions and the length of hospital stay (Reddy et al, 2017). However, there is little evidence focusing on the relationship between intraoperative vasoconstrictor infusion and the prognosis of LT, especially LDLT in children.…”
Section: Introductionmentioning
confidence: 99%